High-entropy copper-based layered composite material and preparation method thereof

By using pre-pressure, laying high-entropy alloy powder, discharge plasma sintering and vacuum diffusion annealing in copper-based layered composite materials, the problem of insufficient bonding of heterogeneous metal materials in the stacking process is solved, and the mechanical properties and interface binding force of the material are significantly improved.

CN119501075APending Publication Date: 2025-02-25CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411579916.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The stacking process has problems in the combination of multilayer materials, especially heterogeneous metal materials, and the interfacial bonding quality is difficult to control, layer and intimate bonding, resulting in a decrease in the mechanical properties and stability of the composite material.

Method used

The pure copper metal powder layer is first pre-formed, and then a high-entropy alloy powder layer is uniformly laid on the surface of the pre-formed pure copper metal powder layer, and discharge plasma sintering and vacuum diffusion annealing are performed after secondary pre-pressure to form a high-entropy copper base layer-like composite material.

Benefits of technology

The interface metallurgical bonding force of high-entropy copper base layer composite materials is significantly improved, the interfacial particle dispersion phenomenon is reduced, and the mechanical properties of the material and the interfacial layer hardness are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119501075A_ABST
    Figure CN119501075A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of copper-based layered composite materials, in particular to a high-entropy copper-based layered composite material and a preparation method thereof. Different metal materials are subjected to layered compounding by adopting a stacking process, the metallurgical bonding force between adjacent metal layers at the interface bonding position of the obtained composite material is insufficient, and layering is easy to occur. In order to solve the problems, the invention provides the high-entropy copper-based layered composite material, the pure copper metal powder layer is firstly subjected to pre-pressing molding, then the high-entropy alloy powder layer is uniformly laid on the surface of the pre-pressed and molded pure copper metal powder layer, and metallurgical compounding is carried out, so that the obtained high-entropy copper-based layered composite material is better in mechanical property; the hardness is higher, and the interface metallurgical bonding force between the adjacent metal interface layers is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-based layered composite materials, and in particular to a high-entropy copper-based layered composite material and a preparation method thereof. Background Art

[0002] With the growing demand for high-performance composite materials, metal-based multilayer composite materials have shown broad application potential in aerospace, electronics, thermal management, energy and other related fields due to their excellent mechanical and physical properties. High-performance materials are not only required to have excellent mechanical strength and plasticity, but also good electrical conductivity, thermal conductivity and corrosion resistance to cope with complex working environments. In this context, metal-based multilayer composite materials have gradually become the focus of research and application due to their structural diversity and controllable performance. By combining metal materials with different properties in a layered form, metal-based multilayer composite materials can achieve an excellent balance in mechanical properties, electrical conductivity and thermal stability that cannot be achieved by a single material, especially in high-end application fields such as microelectronic packaging, heat dissipation devices and conductive components.

[0003] As a new type of multi-principal alloy, high entropy alloy exhibits extremely high strength, hardness and thermal stability, and can significantly improve the mechanical properties of composite materials. The traditional preparation method of layered composite materials is mainly based on the stacking process. The stacking process forms a multi-layer composite structure by stacking different metal layers and then applying high pressure rolling. This process is easy to operate, suitable for large-scale production, and can achieve the composite of multiple metals. However, the stacking process has significant shortcomings in the bonding of multi-layer materials, especially heterogeneous metal materials. The interface bonding quality is difficult to control during the stacking process, and stratification and loose bonding are prone to occur. Especially at the interface of heterogeneous materials, there are often problems such as insufficient metallurgical bonding and enhanced interface brittleness, which leads to a decrease in the mechanical properties and stability of the composite material. In addition, the temperature and pressure control accuracy of the stacking process is limited, making it difficult to achieve precise regulation of the material interface and internal structure, further affecting the comprehensive performance of the material. Summary of the invention

[0004] The problem in the prior art is that different metal materials are laminated by a stacking process, and the metallurgical bonding strength between adjacent metal layers at the interface of the obtained composite material is insufficient, and delamination is easy to occur. In view of the above problem, the present invention provides a high entropy copper-based laminated composite material, and the preparation method thereof comprises the following steps:

[0005] (1) Weigh pure copper powder and place it in a graphite mold surrounded by carbon paper. After oscillation, pre-press the pure copper powder in the graphite mold from top to bottom to obtain a pure copper metal layer. The pre-pressing pressure is 5-10 MPa and the pre-pressing time is not less than 5 min.

[0006] (2) After the first pre-pressing is completed, high entropy alloy powder is evenly laid on the upper surface of the pure copper metal layer, and then a layer of carbon paper is covered on the upper surface of the high entropy alloy powder. Then, the material in the graphite mold is pressed from top to bottom at a pressure of 20-30 MPa for a pressing time of not less than 10 min.

[0007] (3) After step (2) is completed, the entire graphite mold is placed in a spark plasma sintering system furnace chamber for plasma sintering, the sintering temperature is 750° C.-950° C., the holding time is 10-20 min, and the sintering pressure is 30-50 MPa;

[0008] (4) After the sintering in step (3) is completed, the graphite mold is removed and demolded, and the carbon paper on the surface of the obtained layered composite material is polished off with sandpaper to obtain a sintered composite material;

[0009] (5) Placing the sintered composite material obtained in step (4) in a vacuum tube furnace for vacuum diffusion annealing at a temperature of 350-550°C for a time of 1-2 h.

[0010] Preferably, the purity of the pure copper powder is 99.9%.

[0011] Preferably, the average particle size of the pure copper powder is 30-40 μm.

[0012] Preferably, the high entropy alloy powder is prepared by gas atomization.

[0013] Preferably, the high entropy alloy powder is FeCoCrNi high entropy alloy powder.

[0014] Preferably, the mass ratio of pure copper powder to high entropy alloy powder is 1:1-2:1.

[0015] The present invention has the following beneficial effects:

[0016] (1) The high entropy copper-based composite material obtained by the present invention has good interface metallurgical bonding strength, is not prone to interface particle dispersion, and has a high hardness of the interface layer of the composite material;

[0017] (2) The present invention pre-presses the pure copper metal powder layer, then evenly lays a high entropy alloy powder layer on the surface of the pre-pressed pure copper metal powder layer, and sintering is performed after secondary pre-pressing. The obtained high entropy copper-based matrix composite material has better mechanical properties, higher hardness, and better interface bonding strength between adjacent metal interface layers.

[0018] (3) After the composite material is subjected to spark plasma sintering, the composite material is subjected to vacuum diffusion annealing treatment, and the obtained high entropy copper-based composite material has better mechanical properties, which is beneficial to further improve the interface bonding force between adjacent metal layers.

[0019] Figure 1 : Interface OM image of the composite layered material obtained in Example 1.

[0020] Figure 2 : Interface OM image of the composite layered material obtained in Comparative Example 1. DETAILED DESCRIPTION

[0021] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.

[0022] The spark plasma sintering system used in the following embodiments of the present invention is a Labox-325X desktop spark plasma system purchased from Sinter land Co., Ltd. of Japan.

[0023] The high entropy alloy powder used in the following examples of the present invention is FeCoCrNi high entropy alloy powder prepared by gas atomization method, purchased from Ji Ruike Metal Materials (Shandong) Co., Ltd., with an average particle size of 45 μm.

[0024] Example 1

[0025] A high entropy copper-based composite material, the preparation method of which is as follows:

[0026] (1) Weigh 8 g of pure copper powder and place it in a graphite mold with carbon paper on all sides. After oscillation, pre-press the pure copper powder in the graphite mold from top to bottom to obtain a pure copper metal layer. The pre-pressing pressure is 5 MPa and the pre-pressing time is 5 min.

[0027] (2) After the first pre-pressing is completed, 4.5 g of high entropy alloy powder is evenly laid on the upper surface of the pure copper metal layer, and then a layer of carbon paper is covered on the upper surface of the high entropy alloy powder. Then, the material in the graphite mold is pre-pressed from top to bottom for a second time, with a pressure of 20 MPa and a pressing time of 10 min.

[0028] (3) After step (2) is completed, the entire graphite mold is placed in a spark plasma sintering system furnace chamber for plasma sintering at a sintering temperature of 850° C., a sintering time of 10 min, and a sintering pressure of 30 MPa;

[0029] (4) After the sintering in step (3) is completed, the graphite mold is taken out and demolded, and the carbon paper on the surface of the obtained layered composite material is polished off with sandpaper to obtain a high entropy copper-based layered composite material.

[0030] The purity of the pure copper powder is 99.9%, and the average particle size is 30 μm.

[0031] Example 2

[0032] A high entropy copper-based composite material, the preparation method of which is as follows:

[0033] (1) Weigh 8 g of pure copper powder and place it in a graphite mold with carbon paper on all sides. After oscillation, pre-press the pure copper powder in the graphite mold from top to bottom to obtain a pure copper metal layer. The pre-pressing pressure is 5 MPa and the pre-pressing time is 5 min.

[0034] (2) After the first pre-pressing is completed, 4.5 g of high entropy alloy powder is evenly laid on the upper surface of the pure copper metal layer, and then a layer of carbon paper is covered on the upper surface of the high entropy alloy powder. Then, the material in the graphite mold is pre-pressed from top to bottom for a second time, with a pressure of 20 MPa and a pressing time of 10 min.

[0035] (3) After step (2) is completed, the entire graphite mold is placed in a spark plasma sintering system furnace chamber for plasma sintering at a sintering temperature of 950° C., a sintering time of 20 min, and a sintering pressure of 50 MPa;

[0036] (4) After the sintering in step (3) is completed, the graphite mold is removed and demolded, and the carbon paper on the surface of the obtained layered composite material is polished off with sandpaper to obtain a sintered composite material;

[0037] (5) placing the sintered composite material obtained in step (4) in a vacuum tube furnace for vacuum diffusion annealing at a temperature of 350° C. for 1 h to obtain the composite material.

[0038] The purity of the pure copper powder is 99.9% and the average particle size is 30 μm.

[0039] Example 3

[0040] A high entropy copper-based composite material, the preparation method of which is as follows:

[0041] (1) Weigh 8 g of pure copper powder and place it in a graphite mold with carbon paper on all sides. After oscillation, pre-press the pure copper powder in the graphite mold from top to bottom to obtain a pure copper metal layer. The pre-pressing pressure is 5 MPa and the pre-pressing time is 5 min.

[0042] (2) After the first pre-pressing is completed, 4.5 g of high entropy alloy powder is evenly laid on the upper surface of the pure copper metal layer, and then a layer of carbon paper is covered on the upper surface of the high entropy alloy powder. Then, the material in the graphite mold is pre-pressed from top to bottom for a second time, with a pressure of 20 MPa and a pressing time of 10 min.

[0043] (3) After step (2) is completed, the entire graphite mold is placed in a spark plasma sintering system furnace chamber for plasma sintering at a sintering temperature of 950° C., a sintering time of 20 min, and a sintering pressure of 50 MPa;

[0044] (4) After the sintering in step (3) is completed, the graphite mold is removed and demolded, and the carbon paper on the surface of the obtained layered composite material is polished off with sandpaper to obtain a sintered composite material;

[0045] (5) placing the sintered composite material obtained in step (4) in a vacuum tube furnace for vacuum diffusion annealing at a temperature of 550° C. for 1 h to obtain the composite material.

[0046] The purity of the pure copper powder is 99.9% and the average particle size is 30 μm.

[0047] Example 4

[0048] A high entropy copper-based composite material, the preparation method of which is as follows:

[0049] (1) Weigh 8 g of pure copper powder and place it in a graphite mold with carbon paper on all sides. After oscillation, pre-press the pure copper powder in the graphite mold from top to bottom to obtain a pure copper metal layer. The pre-pressing pressure is 5 MPa and the pre-pressing time is 5 min.

[0050] (2) After the first pre-pressing is completed, 4.5 g of high entropy alloy powder is evenly laid on the upper surface of the pure copper metal layer, and then a layer of carbon paper is covered on the upper surface of the high entropy alloy powder. Then, the material in the graphite mold is pre-pressed from top to bottom for a second time, with a pressure of 20 MPa and a pressing time of 10 min.

[0051] (3) After step (2) is completed, the entire graphite mold is placed in a spark plasma sintering system furnace chamber for plasma sintering at a sintering temperature of 950° C., a sintering time of 20 min, and a sintering pressure of 50 MPa;

[0052] (4) After the sintering in step (3) is completed, the graphite mold is removed and demolded, and the carbon paper on the surface of the obtained layered composite material is polished off with sandpaper to obtain a sintered composite material;

[0053] (5) placing the sintered composite material obtained in step (4) in a vacuum tube furnace for vacuum diffusion annealing at a temperature of 550° C. for 2 h to obtain the composite material.

[0054] The purity of the pure copper powder is 99.9% and the average particle size is 30 μm.

[0055] Example 5 is the same as Example 2, except that the pre-pressing pressure in step (1) of Example 5 is 10 MPa and the pre-pressing time is 5 min. The high entropy copper-based matrix composite material obtained in Example 5 has a tensile strength of 251.26 MPa and an elongation at break of 18.26%.

[0056] Example 6 is the same as Example 2, except that in step (2) of Example 6, the pre-pressing pressure is 30 MPa and the pre-pressing time is 10 min.

[0057] Comparative Example 1 is the same as Example 2, except that the high entropy copper-based composite material in Comparative Example 1 is prepared by the following method:

[0058] (1) Weigh 8 g of pure copper powder and place it in a graphite mold with carbon paper on all sides. After oscillation, evenly spread 4.5 g of high entropy alloy powder on the upper surface of the pure copper metal layer, and then cover the upper surface of the high entropy alloy powder with a layer of carbon paper. Then, pre-press the material in the graphite mold from top to bottom with a pressure of 20 MPa for 10 min.

[0059] (2) After step (1) is completed, the entire graphite mold is placed in a spark plasma sintering system furnace chamber for plasma sintering at a sintering temperature of 950° C., a sintering time of 20 min, and a sintering pressure of 50 MPa;

[0060] (3) After the sintering in step (2) is completed, the graphite mold is removed and demolded, and the carbon paper on the surface of the obtained layered composite material is polished off with sandpaper to obtain a sintered composite material;

[0061] (4) placing the sintered composite material obtained in step (3) in a vacuum tube furnace for vacuum diffusion annealing at a temperature of 350° C. for 1 h to obtain the composite material.

[0062] Performance Testing

[0063] The copper-based composite materials obtained in the above embodiments and comparative examples of the present invention were subjected to relevant performance tests, and the test results are shown in Table 1.

[0064] Hardness of Cu layer, interface layer and HEA (high entropy alloy) layer: Vickers hardness was measured using a HXD-1000TMC Vickers hardness tester with a controlled load of 50 gf and a full load time of 15 s.

[0065] Tensile strength and elongation at break: The tensile test was carried out using a WDW-200 universal testing machine, with the tensile strain rate set at 2×10 -4 / s.

[0066] Table 1

[0067]

[0068] Combined with the test data in Table 1, the analysis is as follows:

[0069] The test data of this patent shows that different pre-pressing methods and annealing conditions have a significant impact on the interface bonding and mechanical properties of high entropy copper-based composite materials. The performance improvement is mainly attributed to the optimization of interface bonding and the reduction of microscopic defects. Figure 1 , Instruction Manual Figure 2 The interface conditions of the high entropy copper-based composite materials obtained in Example 2 and Comparative Example 1 respectively, the interface bonding of the composite material is smoother after the secondary pre-pressing, while the dispersion of raw material powder particles appears in many places of the interface after only one pre-pressing, and seriously affects the performance of the composite material. After the secondary pre-pressing (such as Example 1), the tensile strength reaches 384.23MPa, and the elongation at break reaches 19.48%. The secondary pre-pressing (Examples 1-6) increases the contact area between the interfaces by first compacting the copper powder layer, then evenly paving the high entropy alloy powder layer, and applying pressure to the high entropy alloy layer for secondary re-pressing, which promotes the bonding of the high entropy alloy layer and the copper layer. The double compaction significantly reduces the interface defects, strengthens the metallurgical bonding, avoids the early fracture of the copper layer, and significantly improves the hardness and overall strength of the interface layer. The mechanical properties are significantly better than those of Comparative Example 1 (216.28MPa, 15.16%) with only one pre-pressing, which lays the foundation for the high strength and ductility of the layered composite material. This process further improves the material properties under annealing treatment. For example, the interface hardness of Example 3 and Example 4 reaches 131.79 HV 0.05 and 137.12HV 0.05 , the tensile strength is 360.31MPa and 394.71MPa respectively, and the elongation at break is 20.72% and 23.44%. The synergistic effect of secondary preloading and annealing accelerates the atomic diffusion and grain boundary migration at the interface, and promotes the metallurgical bonding of the copper substrate layer and the high entropy alloy layer. The regulation of annealing temperature and time can reduce internal stress, make the interface transition smoother, and reduce crack propagation caused by interface brittleness. Ultimately, the hardness, strength and ductility of the composite material are comprehensively improved, giving it excellent structural and mechanical stability.

[0070] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A high entropy copper-based composite material, characterized in that The preparation method comprises the following steps: (1) Weigh pure copper powder and place it in a graphite mold surrounded by carbon paper. After oscillation, pre-press the pure copper powder in the graphite mold from top to bottom to obtain a pure copper metal layer. The pre-pressing pressure is 5-10 MPa and the pre-pressing time is not less than 5 min. (2) After the first pre-pressing is completed, high entropy alloy powder is evenly laid on the upper surface of the pure copper metal layer, and then a layer of carbon paper is covered on the upper surface of the high entropy alloy powder. Then, the material in the graphite mold is pressed from top to bottom at a pressure of 20-30 MPa for a pressing time of not less than 10 min. (3) After step (2) is completed, the entire graphite mold is placed in a spark plasma sintering system furnace chamber for plasma sintering, the sintering temperature is 750°C-950°C, the holding time is 10-20 minutes, and the sintering pressure is 30-50MPa; (4) After the sintering in step (3) is completed, the graphite mold is removed and demolded, and the carbon paper on the surface of the obtained layered composite material is polished off with sandpaper to obtain a sintered composite material; (5) Placing the sintered composite material obtained in step (4) in a vacuum tube furnace for vacuum diffusion annealing at a temperature of 350-550°C for a time of 1-2 h.

2. A high entropy copper-based composite material according to claim 1, characterized in that: The purity of the pure copper powder is 99.9%.

3. A high entropy copper-based composite material according to claim 2, characterized in that: The average particle size of the pure copper powder is 30-40 μm.

4. A high entropy copper-based composite material according to claim 1, characterized in that: The high entropy alloy powder is prepared by gas atomization.

5. A high entropy copper-based composite material according to claim 4, characterized in that: The high entropy alloy powder is FeCoCrNi high entropy alloy powder.

6. The high entropy copper-based composite material according to claim 1, characterized in that: The mass ratio of pure copper powder to high entropy alloy powder is 1:1-2:1.